DEVELOPMENT OF RESPONSIBILITY ATTITUDES ASSESSMENT INSTRUMENT FOR INTEGRATED THEMATIC LEARNING OF GRADE III - Radia, Elvira Hoesein (Journal of Education Research and Evaluation, 2021)
The aims of the research and development are to (1) produce an instrument for assessing responsibility attitudes of integrated thematic learning theme 4 sub-theme 1 5th learning for grade III elementary school. (2) measuring the level of validity and reliability of the instrument for assessing responsibility attitudes of integrated thematic learning theme 4 sub-theme 1 5th learning for grade III elementary school. The type of research is development research that refers to the Borg and Gall theory by applying the ADDIE development model. The population of this research is the third-grade students of the National Elementary School of Karanganyar 2 Karangrayung. The sample was determined using a random sampling technique with a sample of 23 students. The data collection technique used was a questionnaire instrument using a Likert scale. The results showed that the social attitude instrument of 30 (thirty) statement items obtained data; reliability of the instrument for assessing responsibility attitudes of integrated thematic learning theme 4 sub-theme 1 5th learning for grade III elementary school shows Î± = 0.758 then the instrument is categorized as very reliable; the validity level of the instrument shows the lowest rcount is 0.411, has a Pearson Correlation XTot value â‰¥ 0.3961 so that the instrument is categorized as valid and suitable for use.